2017
DOI: 10.1136/bmjopen-2016-015676
|View full text |Cite
|
Sign up to set email alerts
|

Are medical outliers associated with worse patient outcomes? A retrospective study within a regional NHS hospital using routine data

Abstract: ObjectiveTo explore the quality and safety of patients’ healthcare provision by identifying whether being a medical outlier is associated with worse patient outcomes. A medical outlier is a hospital inpatient who is classified as a medical patient for an episode within a spell of care and has at least one non-medical ward placement within that spell.Data sourcesSecondary data from the Patient Administration System of a district general hospital were provided for the financial years 2013/2014–2015/2016. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 19 publications
3
40
0
Order By: Relevance
“…While the Charlson scores, length of stay and in-hospital mortality rates in their study are similar to those reported from other Canadian university hospitals with similar GIM service distributions,12 this study definitely needs to be replicated in other settings. While one American study13 reported that localising GIM patients to home wards improved workflow efficiency but increased length of stay and mortality, we12 found that cohorting our GIM patients on home wards rather than having them bedspaced throughout our institution resulted in substantially shorter lengths of stay without any impact on mortality—similar to a study in a UK district general hospital 6. Interestingly, we also found no impact on ED wait times or crowding metrics, suggesting that the potential benefits of inpatient bedspacing for EDs are smaller than assumed 14…”
supporting
confidence: 57%
“…While the Charlson scores, length of stay and in-hospital mortality rates in their study are similar to those reported from other Canadian university hospitals with similar GIM service distributions,12 this study definitely needs to be replicated in other settings. While one American study13 reported that localising GIM patients to home wards improved workflow efficiency but increased length of stay and mortality, we12 found that cohorting our GIM patients on home wards rather than having them bedspaced throughout our institution resulted in substantially shorter lengths of stay without any impact on mortality—similar to a study in a UK district general hospital 6. Interestingly, we also found no impact on ED wait times or crowding metrics, suggesting that the potential benefits of inpatient bedspacing for EDs are smaller than assumed 14…”
supporting
confidence: 57%
“…Observed care delays in outliers and patients with multiple care teams were a result of confusion regarding plans, responsibilities, and delayed decisions. These factors may partially explain why there is evidence that outliers have higher readmission rates and length of stay . There may be value in identifying high‐risk patients (complex patients, outliers, or patients with multiple teams) and mitigating this with a systematic approach to care, such as clear documentation or pre‐planned care escalation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Santamaria et al 8 reported a mortality increase among outliers in general and Perimal-Lewis et al 6 among outliers affected by dementia. These data were refuted by Stowell et al 10 and by Stylianou et al 1 on large numbers (over 70,000 admissions in 3 years of observation) and by Alameda et al 13 among outliers with heart failure. Stowell et al 10 and Stylianou et al 1 examined also 30-day mortality without finding any increase; Perimal et al 6,9 instead revealed a nonsignificant increase in outliers.…”
Section: A Mortalitymentioning
confidence: 95%
“…The so-called outlier, out-lying hospital in-patient, overflow, sleep-out, or boarder [1][2][3] is a patient who, because of unavailability of hospital beds in his/her clinically appropriate ward, is admitted wherever an unoccupied bed is. In such a case, clinical management is provided by the medical staff of the clinically appropriate ward (generally, internal medicine), but care is delivered by nursing staff of the hosting ward.…”
Section: Introductionmentioning
confidence: 99%